IRONI PENCARIAN HOLY GRAIL DALAM NOVEL THE DA VINCI CODE KARYA DAN BROWN - PUNI, RUSLI (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI)
ABSTRACT This skripsi entitled â€œThe Irony In Searching The Holy Grail In Novel The Da Vinci Code by Dan Brownâ€ is intended to be one of the requirements to accomplish the Sarjana tittle at Faculty Of Humanities, University Of Sam Ratulangi Manado.Â The aims of this research are to identify, classify and analyze the irony and how they are illustrated in searching the Holy Grail and identify and analyze the placement of irony in searching the Holy Grail in novel The Da Vinci Code by Dan Brown.Â In conducting this research, the methodology used is descriptive method by Winarno (1984). The approach used in this research is intrinsic approach by Wellek and Warren (1977). Theory of irony by Landy (1972), the classification of irony from theory of Edgar V. Roberts (1983) and theory of plot by Tasrif (in Nurgiyantoro:2002) are used to do the analysis.Â Â The results of this research show that the irony and its three types: verbal irony, dramatic irony and irony of situation are found in the novel. Verbal irony is illustrated through the character of Andre Vernet. Dramatic irony is illustrated through the characterâ€™s statement of Teacher. Situational irony is illustrated through the character of Aringarosa. The analysis of the placement of irony shows that the irony elements are placed in rising action, climax and resolution. In rising action, the irony found is verbal irony through the character of Andre Vernet. In climax, the irony found is dramatic irony through the characters of The Teacher and Remy. In resolution, the irony found is situational irony through the character of bishop Aringarosa. Keywords: Irony, Searching The Holy Grail, Plot, The Da Vinci Code